Dialog kultur drogą do lepszego zrozumienia przeszłości i teraźniejszości = Dialogue of cultures as a path to better understanding the past and present - Kobyłecka, Alina; Kobyłecka-Bitner, Paulina; Niewiński, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents the activities of the scientific group "In Dialogue". Its members participate in various events (e.g. artistic, social, educational) to better understand representatives of other cultures. They also promote knowledge about multiculturalism, encouraging an open attitude towards national and ethnic minorities. They participate in scientific conferences, prepare speeches and publications, too.
Keywords: dialog kultur; tolerancja; wielokulturowość; dialogue of cultures; tolerance; multiculturalism